Non Linear Finite Element Modeling of Reinforced Concrete Flat Plate Slabs with openings - Rafiq, Serwan Khorshid (Sulaimani Journal for Engineering Sciences, 2017)
In this study, a model using ABAQUS/ EXPLICIT program to predict punching shear resistance of reinforced concrete flat plates was proposed with opening in different situation subjected to vertical loading. A three dimensional non-linear finite element program (ABAQUS/EXPLICIT) based on Eight-Nodes hexahedral element damage-plasticity was utilized for modeling concrete with opening, in this investigation. Reinforcing bars were represented by one dimensional element embedded in the solid elements and for both tension and compression linear elastic-plastic behavior is assumed. Nonlinear analysis is used and the result of finite element shows good agreement with the experimental results.
Keywords: Finite Element; Flat Plate Slabs; Abaqus/ Explicit